Internal control of Telekom Malaysia's Treasury Unit / Azhar Ahmad - Ahmad, Azhar (1991)
Formerly, emphasis in a business operation is the object of getting work done by the quickest and cheapest method available, but while these objects are maintained, it has been realised that the establishment of piecemeal methods of uncoordinated work process is untimely neither cheap nor efficient. This lead to establishment of an overall plan that is necessary to ensure a flow of Work through the whole business, enabling it to run smoothly and efficiently and at the same time the assets are safeguarded. This overall plan and its practical operation are known as Internal Control.